Prototype Innovation of IOT Based Tissue Box Using Microcontroller ESP8266 and Infrared Sensor - Yesy Diah Rosita; Nuuraan Risqi Amaliah; Andhika Cahyono Putra; Fikra Titan Syifa; Nur Azizah (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
Toilet papers in public restrooms are a form of care from facility managers to help maintain hygiene, particularly in sensitive areas. Typically, toilet paper is exposed outside the tissue box, making it a breeding ground for bacteria. The uncontrolled use of tissue allows users to take as much as they wish, indirectly accelerating deforestation. Additionally, information about tissue stock in toilet paper dispensers is needed by cleaning staff or Office Boy (OB) to know when to refill before it runs out. This study aims to develop an innovative tissue box prototype that incorporates minimization, optimization, and efficiency. The prototype is equipped with an infrared (IR) sensor as an input mechanism to dispense tissue, an ESP8266 module connected to the internet to help cleaning staff monitor the tissue stock and implement the tissue usage control system based on an adjustable time interval of n minutes. The prototype has been designed, tested, and proven functional.